Intensification of engineering and design training of students - Melkozerovа Людмила (Рroblems of engineering and professional education, 2022)
The article is dedicated to solving the problem of improving the professional qualification (quality) of training students based on the use of information technologies, especially in the KOMPAS system. Functional features of KOMPAS for determining the degree of design calculation are described.